Development and initial validation of the perceived instrumental effects of violence in sport scale - Parent, Sylvie; Radziszewski, Stephanie; Gillard, Allyson; Bélanger-Gravel, Ariane; Gagné, Marie-Hélène; St-Pierre, Elisabeth; Vertommen, Tine; Woodburn, Andrea (Frontiers in Sports and Active Living, 2024)
Introduction A growing body of research is looking into risk factors for interpersonal violence (IV) in sport. This research suggests the existence of several important risk factors, especially organizational and social factors. One of these factors is the beliefs regarding instrumental effects of violence. Coaches may want to drive performance, deter failure, test resilience and commitment, develop toughness, assure interpersonal control, and promote internal competition. In sum, available evidence suggests the risk of IV increases when coaches believe in the effectiveness of strategies involving IV to enhance athlete performance or perceive external approval for these practices. Methods The studies presented in this article seeks to develop and validate the Perceived Instrumental Effects of Violence in Sport (PIEVS) Scale in order to measure those beliefs in coaches. In study 1, item generation, expert consultation, cognitive interviews, pilot test and item reduction phases led to 25 items for the PIEVS around six dimensions. In study 2, exploratory factor analysis (EFA) was conducted with 690 coaches in order to determine the PIEVS factorial structure and the convergent and divergent validity of the scale was tested (long and short form). Results Our results suggested a one-factor solution for the PIEVS (25 items). This one-factor model provided an excellent fit to the data and a very good internal consistency. The PIEVS and empowering motivational climate were negatively correlated, which supported divergent validity as expected. The PIEVS was positively correlated with the disempowering motivational climate and with sport ethic norms, which supported convergent validity as expected. Discussion These findings provide preliminary evidence for the appropriateness of the PIEVS Scale to measure perceived instrumental effects of violence in coaches.